M. NATSIR DAN GERAKAN KRISTENISASI DI INDONESIA 1965-1979 - Indria Jami'atul Rohmah (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2019)
Abstract: This article examines M. Natsir's actions regarding efforts to Christianize Indonesia. Has three research focuses, namely: What is the biography of Muhamad Natsir. What is the history of the development and impact of Christianization for Muslims in Indonesia in 1965-1979. What actions did Muhamad Natsir take in facing the Christianization of 1965-1979. This research is a library research using descriptive analysis with a historical-sociological approach. In writing this thesis the author uses historical research methods with the following steps: Heuristics (collecting data), Verification (criticizing data), Interpretation (interpretation of data) and Historiography (Writing of History). The writing of this thesis uses a historical-sociological approach. This approach is used by researchers to produce forms and processes of historical events, in addition to explaining the actions taken by Muhamad Natsir in dealing with Christianization in Indonesia in 1965-1979. From the results of the study it can be concluded that: (1) Muhamad Natsir is a contemporary Islamic figure who is quite influential in Indonesia (2) the development of Christians has increased rapidly after the outbreak of the G30S/PKI conflict, the spread of Christianity in Indonesia has drawn many protests from Muslims because too aggressive, and considered intolerant of members of other religions (3) The efforts made by M. Natsir in dealing with this Christianization were, proposing a modus viviendi as a way out, sending personnel from the Indonesian Islamic Da'wah Council to remote and rural areas in Indonesia. Keywords: M. Natsir, conflict, Cristianization, interfaith relations